Analisis Pengaruh Rapor Satuan Pendidikan dan Supervisi Akademik dengan Kinerja Guru Sekolah Menengah Pertama di Kecamatan Amahai - Fretes, Elsa Beatrix De; Ratumanan, T.G.; Lokollo, I. J.; Rumfot, Sumarni (LP. Ma'arif Janggan Magetan, 2024)
The success of educational institutions can be seen from the school reports and is supported by teachers' knowledge of school reports to create and generate recommendation programs supported by the improvement of the quality of learning through academic supervision. This research aims to (1) Describe the knowledge of junior high school teachers in Amahai Subdistrict about school reports. (2) Describe academic supervision of junior high school teachers in Amahai Subdistrict. (3) Describe the performance of junior high school teachers in Amahai Subdistrict. (4) Describe the significant influence of teachers' knowledge of school reports on the performance of junior high school teachers in Amahai Subdistrict. (5) Describe the significant influence of academic supervision on the performance of junior high school teachers in Amahai Subdistrict. (6) Describe the significant influence of teachers' knowledge of school reports and academic supervision together on the performance of junior high school teachers in Amahai Subdistrict. This research is quantitative in nature. The sample was obtained from SMP Negeri 40 Maluku Tengah, SMP PGRI Rutah, SMP Kristen Haruru, SMP Negeri 68 Maluku Tengah, and SMP Al-Hilaal Yainuello, with a total of 68 respondents. Data for this research were collected through questionnaire surveys. Data analysis was conducted using regression analysis. The results of the descriptive analysis show that teachers' knowledge of school reports among junior high school teachers in Amahai Subdistrict is very high for 40 teachers, or 59%, and high for 28 teachers, or 41%. Academic supervision among junior high school teachers in Amahai Subdistrict is high for 37 teachers, or 54%, and sufficient for 31 teachers, or 46%. The performance of junior high school teachers in Amahai Subdistrict is very high for 40 teachers, or 59%, and high for 28 teachers, or 41%. There is a positive and significant influence of knowledge of school reports on the performance of junior high school teachers in Amahai Subdistrict (Sig = 0.000), with a coefficient of determination (R Square) of 0.539 or 53.9%. There is a positive and significant influence of academic supervision on the performance of junior high school teachers in Amahai Subdistrict (Sig = 0.000), with a coefficient of determination (R Square) of 53.9%. There is a positive and significant influence of both teachers' knowledge of school reports (X1) and academic supervision (X2) together on the performance of teachers (Y) in junior high schools in Amahai Subdistrict (Sig = 0.000), with a coefficient of determination (R Square) of 55.0%. It can be concluded that teachers' knowledge of school reports and academic supervision collectively influence the performance of junior high school teachers in Amahai Subdistrict. Therefore, it is hoped that relevant parties will reconsider efforts to improve teacher performance in schools so that educational goals can be maximally achieved.